Statutory mergers as contemplated in the Companies Act, 2008: the applicability of the corporate rules contained in section 44 of the Income Tax Act, 1962 - Shama, Natalie Anne (Rhodes University, Faculty of Commerce, Department of Accounting, 2020)
The purpose of this research is to determine the extent to which a statutory merger in terms of the Companies Act, 2008, may be accommodated by the provisions of an amalgamation transaction in terms of section 44 of the Income Tax Act, 1962. The research method adopted is a legal interpretative research approach. South African company law underwent significant reform with the introduction of the Companies Act, 2008. One of the fundamental areas for reform was the need for a mechanism to appropriately accommodate a corporate merger, and thus, what is referred to as a statutory merger was introduced into South African company law. What is notable is that the statutory merger has been crafted to apply across a variety of circumstances that may arise in commerce, thus offering wide versatility. On the other hand, the tax relief afforded in terms of the corporate roll-over provisions in the Income Tax Act is designed to facilitate corporate transactions on a tax neutral basis, whilst balancing the concessions these measures introduce and the potential for tax avoidance. Consequently, the tax relief applicable to an amalgamation transaction will only apply within strictly prescribed parameters. The research shows an ongoing effort by National Treasury to amend the provisions of the amalgamation transaction to better accommodate a statutory merger, but highlights that there are nevertheless certain conflicting purposes (policy) for each piece of legislation. For these reasons, the focus and parameters of a statutory merger and amalgamation transaction do not align perfectly. The key areas of inconsistency identified in this research are threefold, namely (i) the creation of a new company as a consequence of a statutory merger is not accommodated in an amalgamation transaction; (ii) the process of compensating the shareholders of the amalgamated company in an amalgamation transaction is not clearly contemplated in the statutory merger provisions; and (iii) mergers between a company and its shareholder currently present numerous complexities from both a company law and taxation perspective. The research concludes that the flexibility afforded under the statutory merger is largely minimised for parties who wish to simultaneously enjoy the tax relief afforded under an amalgamation transaction.
Keywords: South Africa. Companies Act, 2008; South Africa. Income Tax Act, 1962; Consolidation and merger of corporations -- South Africa; Corporation law -- South Africa